Bioactivity screening of five Centaurea species and in vivo anti-inflammatory activity of C. athoa. (June 2014) - Erel, Sura Baykan; Demir, Serdar; Nalbantsoy, Ayse; Ballar, Petek; Khan, Shabana; Yavasoglu, N. Ulku Karabay; Karaalp, Canan
Abstract Context: Centaurea L. (Asteraceae) species used as herbal remedies in Turkish traditional medicine have shown several biological properties. Objective: Extracts obtained from the aerial parts of Centaurea aphrodisea Boiss., Centaurea athoa DC., Centaurea hyalolepis Boiss., Centaurea iberica Trev. and Centaurea polyclada DC. were evaluated for their antioxidant, cytotoxic and anti-inflammatory activities. Materials and methods: Extracts of Centaurea species were tested for their antioxidant activity in the 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and 2, 2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid (ABTS) screening assays and for in vitro anti-inflammatory activity by Nf-κB and iNOS inhibition assays. The extracts were tested for their in vitro cytotoxicities against a panel of human solid tumor cell lines (SK-MEL: malignant melanoma, KB: oral epidermal carcinoma, BT-549: breast ductal carcinoma and SK-OV-3: ovary carcinoma) as well as non-cancerous kidney fibroblast (Vero) and kidney epithelial cells (LLC-PK1) by Neutral Red assay. In vivo anti-inflammatory activity of C. athoa was evaluated by the carrageenan-induced paw edema test in rats. Results: Antioxidant activities were observed for methanol extracts of plants. C. polyclada had the strongest effect on BT-549, KB and SK-OV-3 cell lines (30, 33 and 47 µg/ml, respectively). Nf-κB inhibition of chloroform extract of C. athoa was determined equivalent to positive control parthenolide (IC50: 6 µg/ml). This extract also showed anti-inflammatory activity by the carrageenan-induced paw edema test in rats, in all hours at a dose of 50 mg/kg compared to the control group. Discussion and conclusion: C. athoa is suggested to be a potential source of lead compounds for inflammatory diseases due to the significant in vitro and in vivo anti-inflammatory results.